Stress and Its Association with the Academic Performance of Undergraduate Fourth Year Medical Students at Universiti Kebangsaan Malaysia - Siraj, Harlina H; A, Salam; R, Roslan; NA, Hasan; TH, Jin; MN, Othman (IIUM Medical Journal Malaysia, 2014)
Introduction: Student can be stressed due to different stressors such as academic, financial, health related or loss of close family member or friend, etc. Stress is the bodies’ reaction both neurologically and physiologically to adapt to the new condition. Stress has a negative effect on the academic performance of the students. This study was aimed to explore the stress and stressors and also to determine the association between stress levels and the academic performances in terms of cumulative grade point average (CGPA) of undergraduate medical students. Methods: It was a cross-sectional study conducted among all 234 year-4 medical students of Universiti Kebangsaan Malaysia (UKM), session 2011-2012. Sample size comprised of 179 students after fulfilling all inclusion and exclusion criteria. A validated Medical Students’ Stressor Questionnaire (MSSQ) was used to collect the data. Stress level and its association with CGPA of semester-1 examination were analysed. Results: Response rate was 76.49%, where 72% were female and 69% resided in the hostel. Academic Related and Social-related Stressors caused for severe and high stress in 84% and 49% respondents respectively, with insignificant differences between gender and residency. Respondents with a high and severe stress level were observed to have higher CGPA. Conclusion: UKM medical students are highly resourceful to manage their stress well and thus denying the negative effect of stress towards their academic performance. Medical schools should train students exposing various personal and professional developmental activities that able to face the everyday challenges and manage stress well and thereby achieve better academic performance.